Adsorption properties of the fumed individual and mixed Si, Ti and Al oxides as proxies for the Antarctic atmospheric mineral aerosols - M. S. Bazylevska; V. I. Bogillo (Український антарктичний журнал, 2019)
The aim of the study is to determine the effects of structure and content of X, CX in the oxides X/SiO2 (X = Al2O3, TiO2, Al2O3/TiO2) on the surface characteristics. The low-temperature nitrogen adsorption isotherms on the surface of 12 individual and mixed fumed oxides of Si, Ti and Al, as proxies for the Antarctic  atmospheric mineral aerosols, were measured by volumetric method. The specific surface areas of the oxides, SBET were calculated by using the Brunauer–Emmett–Teller (BET) theory. The dependence between CX and SBET is not obeyed for the mixed oxides, which can be caused by effects of the reaction temperature of MCln (M = Si, Ti and Al) hydrolysis in the oxygen/hydrogen flame and by different concentration ratios of O2, H2 and MCln on the structural characteristics of the primary particles and their aggregates. The N2 adsorption energy distributions of the oxides surface were calculated by the regularization procedure. It was demonstrated that the surfaces are characterized by high energetic heterogeneity. Result. The Zero-Adsorption Isotherm (ZAI) approach was applied to describe the N2 adsorption in the whole range of its pressures. The ZAI derived in approximation of adsorbed vapor as a set of molecular clusters. The specific surface areas for the oxides, As, maximal numbers of the molecules in the adsorbed clusters, thicknesses of the adsorbed liquid film and the free surface energies of the oxides in the absence of adsorption, γS0, were calculated using the ZAI equations. The As correlates well with SBET and it measures 77.5% of the SBET. The γS0 increases as the N2 average adsorption energy grows. The dependence between γS0 and CX (taking into account γS0 for X) is not obeyed for the mixed oxides. The γS0 for SiO2, Al2O3 and TiO2 rises as the permittivity and the index of refraction increase. The γS0 is within the range of dispersive components of free surface energy, which is determined by other experimental methods and calculated using the Lifshitz’ theory. The obtained parameters allow estimate the activity of the oxide surface with respect to trace gases in the Antarctic atmosphere that is necessary for calculating their partition coefficients between particles and the atmosphere and the kinetics of their removal.